Adolescents' Perceptions of Their Consent to Psychiatric Mental Health Treatment. (16th February 2012) - Roberson, Anthony James; Kjervik, Diane K.
Abstract : The purpose of this paper is to present the findings of a small-scale study in which the decision-making process of adolescents who consent to psychiatric mental health treatment was examined. Sixteen (16) adolescents were interviewed about their decisions related to initial and continued treatment, along with their understanding of minor consent laws. Interviews were audio-recorded, and transcripts were analyzed through concept analysis. Findings are presented in the context of the decision-making steps and research questions. Most adolescents did not recognize consequences related to psychiatric mental health treatment and did not assimilate and integrate information provided to them about treatment choices. Adolescents disagreed with current minor consent laws that allow minors to consent to certain healthcare treatments without the required consent of the parent. Further, adolescents reported that a collaborative approach in making decisions about the adolescent's psychiatric mental health treatment was most facilitative of achieving the goals of treatment.